2016
DOI: 10.1111/dom.12795
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of GLP‐1 receptor agonist treatment on body weight in obese antipsychotic‐treated patients with schizophrenia: a randomized, placebo‐controlled trial

Abstract: AimsSchizophrenia is associated with cardiovascular co‐morbidity and a reduced life‐expectancy of up to 20 years. Antipsychotics are dopamine D2 receptor antagonists and are the standard of medical care in schizophrenia, but the drugs are associated with severe metabolic side effects such as obesity and diabetes. Glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) are registered for treatment of both obesity and type 2 diabetes. We investigated metabolic effects of the GLP‐1RA, exenatide once‐weekly, in non‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 47 publications
3
74
0
Order By: Relevance
“…These corrected results correspond to the second paragraph Section 3.2 in the original paper . Changes are shown in italic font.…”
Section: Corrected Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…These corrected results correspond to the second paragraph Section 3.2 in the original paper . Changes are shown in italic font.…”
Section: Corrected Resultssupporting
confidence: 55%
“…“Treatment of antipsychotic‐associated obesity with a GLP‐1 receptor agonist (GLP‐1RA): The TAO trial” was the first clinical investigation of glucagon‐like peptide‐1 receptor agonist (GLP‐1RA) treatment (exenatide 2 mg once‐weekly or placebo) in antipsychotic‐treated schizophrenia patients with obesity . Recently, we published the main results from the TAO trial as an original article in Diabetes, Obesity and Metabolism …”
Section: Biochemical Fasting Blood Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…One study was restricted to participants receiving clozapine and olanzapine, and another to clozapine alone . The third study included a naturalistic patient sample treated with clozapine, olanzapine, aripiprazole, risperidone, paliperidone, quetiapine, ziprasidone, amisulpride and sertindole . After initial publication, an erratum on corrected metabolic blood markers was published for the third study, and these data were used in the current meta‐analysis .…”
Section: Resultsmentioning
confidence: 99%
“…Exenatide may have advantages over daily liraglutide in that it is a once‐weekly injection, increasing the chance of adherence in people on clozapine, especially if they gain confidence in their ability to self‐administer. One trial of weekly exenatide for obese people with schizophrenia showed equivocal results, but that study only ran for 12 weeks and did not limit participants to those on olanzapine or clozapine, the medications most likely to affect the GLP‐1 pathway …”
Section: Discussionmentioning
confidence: 99%